Sosialisasi Pembuatan Nugget Sehat Berbahan Dasar Tempe Di Desa Petangguhan Kecamatan Galang Kabupaten Deli Serdang - Rizki Efrida; Zuli Agustina Gultom; Fahrizal Zulkarnain; Elvira Nuriza Harahap (CERED Indonesia Publishing, 2022)
Tempe is a typical Indonesian food made from fermented soybeans. Tempe is one of the foods that are often consumed by the people of Indonesia. Tempe is a processed protein that is easy to consume because its affordable price. There are many processed tempe menus such as tempe bacem, fried, baked or steamed. along with the time, the creations of processed tempe will be more diverse, one of which is making tempe-based nuggets. Processed nuggets will be increasingly enjoyed by children, because they are tasty and delicious and add protein in the body. This activity done to increase business opportunities in Desa Petangguhan with the majority of farmers, there a great opportunity to improve the economy of Desa Petangguhan. By making nuggets from tempe which taste good, have high nutrition and affordable prices. Training on making tempe nugget was carried out for women from Desa Petangguhan community to increase self-confidence in entrepreneurship. the capital used in making tempe is not too large. This activity is carried out to increase public knowledge about culinary businesses and can increase people's income.